You are on page 1of 13

Week 04 - 05 : Wave Equations

In this chapter, we will consider the ( 1 D) wave equation
u t t − c 2 u x x = 0.

(1)

u( x , t) = f( x + c t) + g( x − c t)

( 2)

As we have seen, the general solution is

with two artibrary functions f and g. In practice, the wave equation describes ( among other phenomena)
the vibration of strings or membranes or propagation of sound waves. In these phenomena obviously there
is no arbitrary functions involved.
Now how do we “fix” the arbitrariness? Remember that for first order PDE ( with two variables) , the
solutions are surfaces in the space. One way to choose one from the infinitely many surfaces is the prescribe one curve in the space and require the solution surface to pass through it. Remember that the coordinates are ( x , y , u) , thus a curve in the space is represented by values of u assigned to a curve ( x( t) ,
y( t) ) . Such a problem is called Cauchy problem.
When we deal with second order equations, it turns out that assigning u along a curve is not enough,
we also need to assign derivatives. To see why, we can rewrite a second order eqution into a system of
first order equations by assigning new variables
v = ux ,

( 3)

w = u y.

Then intuitively to “fix” one solution, we need to assign v , w along the curve too.
In this chapter, we will consider the Cauchy problem for ( mostly 1 D) wave equation
u t t − c 2 u x x = 0.

( 4)

u t t − c 2 u x x = 0,
x ∈ R, t > 0
u( x , 0) = f( x) ,
x∈ R
u t ( x , 0) = g( x) ,
x ∈ R.

( 5)
( 6)
( 7)

1 . D’ Alembert’ s formula.
As a start, we study the simplest one, with u and u t assigned along the x-axis: 1

From past lectures we know that the general solution is
( 8)

φ( x + c t) + ψ( x − c t) .
We would use the values of u , u t along the x-axis to fix the two arbitrary functions φ and ψ. We have
φ( x) + ψ( x) = u( x , 0) = f( x) ,
c φ 0 ( x) − c ψ 0 ( x) = u t ( x , 0) = g( x) .

( 9)
( 1 0)

φ 0 ( x) + ψ 0 ( x) = f 0 ( x)
g( x)
φ 0 ( x) − ψ 0 ( x) =
,
c

(11)

From this we have

whose solutions are 

g( x)
1
φ ( x) =
f 0 ( x) +
2
c 

g( x)
1
ψ 0 ( x) =
f 0 ( x) −
2
c
0

1 . T hink: why is assigning u t enough?

( 1 2)  

,

( 1 3)

.

( 1 4)

0) = sin x . 0) = x 2 . t) = 1 1 [ sin( x + c t) + sin( x − c t) ] + 2 2c Some calculation yields u( x . 2 2 c x − ct ( 24) ( 25) Some calculation gives u( x . ( 20) x − ct Example 1 . t 0 ) + 2 c x − c ( t − t0 ) ( 27) . we can conclude C1 + C2 = 0. 1 2. t) =    i 1h log 1 + ( x + c t) 2 + log 1 + ( x − c t) 2 + 2 t. ( § 5.These give Z 1 1 f( x) + g( x) + C1 2 2cZ 1 1 ψ( x) = f( x) − g( x) + C2 2 2c ( 1 5) φ( x) = Using ( 1 6) ( 1 7) φ( x) + ψ( x) = f( x) again. if we represent u( x . t) = sin x cos c t + x 2 t + y 2 dy.  u( x . From the d’ Alembert formula we see that − the solution u at ( x . we see that the value u( x . 0) = log 1 + x 2 . Zx + ct g( y) dy. t 0 ) + u( x − c ( t − t 0 ) . t) = u( x + c ( t − t 0 ) . 0) respectively. what happens outside the interval ( x − c t. that is Zx 1 1 f( x) + φ( x) = g( y) + C 2 c Z0 2 x 1 1 ψ( x) = f( x) − g( y) − C 2 2c 0 ( 1 8) ( 1 9) As a consequence the solution formula is 1 1 u( x . t) is only affected by what happens inside the cone formed by the two rays from ( x . we have Z x + c ( t − t0 ) 1 u t ( y . This cone is called domain of dependence . x − ct 1 2 3 c t . u t t − c 2 u x x = 0. t) = φ( x + c t) + ψ( x − c t) = [ f( x + c t) + f( x − c t) ] + 2c 2 This is called the d’ Alembert formula . t 0 ) dy. ( 21 ) Zx+ct ( 22) Solution. 1 e) ) Determine the solution. 1 b) ) Determine the solution. u( x . x + c t) does not affect the value u( x . u t t − c 2 u x x = 0. u t ( x . − on the other hand. 0) = 2. ( § 5. 0) and ( x + c t. t) at all. t) passing ( x − c t. t) using values along t = t 0 . u t ( x . Solution. 2 ( 26) ( Note: It is not necessary to further “simplify” as the book did. In other words. u( x . If we do not treat t = 0 specially. 1 2. t) = log 1 + ( x + c t) 2 + log 1 + ( x − c t) 2 + 2 dy. 3 ( 23) Example 2. We use the d’ Alembert formula: u( x . We use the d’ Alembert formula: Zx + ct    i 1h 1 u( x . t) only depends on the values of f at two points x ± c t and the values of g between these two points.

ξx x = ξx y = ξ y y = 0. t 0 ) are only involved in formulas for u( x . ξ y = 1 . x 0 + c ( t − t 0 ) ] . ( d y − 3 dx) ( dy + dx) = 0 ( 29) d( y + x) = 0 ( 30) η = y + x. ( § 5. t) . ( 34) ( 35) ( 36) 0 = ( 9 u ξ ξ − 6 u ξ η + u η η) + 2 ( − 3 u ξ ξ − 2 u ξ η + u η η) − 3 ( u ξ ξ + 2 u ξ η + u η η) = − 1 6 u ξ η. ux y = − 3 u ξ ξ − 2 u ξ η + u η η . ( 37) This gives This transforms the equation to Thus the general solution is u( x . 0) = sin x . and leads to ξ = y − 3 x. ( 40) Taking derivative of the first equation we have − 3 φ 0 ( − 3 x) + ψ 0 ( x) = cos x. 8 4 φ( − 3 x) + ψ( x) = u( x . t) and ( x 0 + c ( t − t 0 ) . 1 2. u x x + 2 u x y − 3 u y y = 0. Thus we can solve φ 0 ( − 3 x) = x − cos x 4 φ 0 ( x) = − x/ 3 − cos( − x/ 3) . 24 4 ψ( x) = 3 x2 1 + sin x + C2 . 0) = sin x . ( 28) Solution. 4) Solve u( x . t) with x ∈ [ x 0 − c ( t − t 0 ) . 0) = x. η y = 1 . η) = φ( ξ) + ψ( η) ( 38) Now the Cauchy data leads to φ( − 3 x) + ψ( x) = u( x . Finally we look at a general hyperbolic Cauchy problem. 4 ( 42) Integrate. what happens at ( x 0 . uyy = uξξ + 2 uξη + uηη .We see that the values u( x 0 . we obtain The Cauchy data φ( x) = − x2 3 + sin( − x/ 3) + C1 . u( ξ. 4 ( 41 ) ψ 0 ( x) = cos x + 3 x . First we need to reduce the equation to canonical form. Or equivalently. y) = φ( y − 3 x) + ψ( y + x) . 0) = sin x ( 43) ( 44) . 0) = x. t 0 ) and u t ( x 0 . t 0 ) passing through ( x 0 − c ( t − t 0 ) . ( 32) ηx = 1 . t 0 ) only affects what happens in the cone formed by the two rays from ( x 0 . η x x = ηx y = η y y = 0. u y ( x . Example 3. ( 31 ) Now we perform the change of variables. ( 39) φ 0 ( − 3 x) + ψ 0 ( x) = u y ( x . The characteristics equation is 2 2 ( dy) − 2 ( dx) ( dy) − 3 ( dx) = 0 which gives d( y − 3 x) = 0. This cone is called the range of influence . ( 33) ux x = 9 u ξ ξ − 6 u ξ η + u η η . Calculate ξx = − 3.

as a consequence we already have all φ( x + c t) we need. We have Z−x 1 1 ψ( x) = − φ( − x) = − f( − x) − g( y) − C . 0 6 x < ∞. 0 6 t < ∞. y) = φ( y − 3 x) + ψ( y + x) = − 2 3 ( y + x) 2 1 ( y − 3 x) 3 + + sin( y + x) + sin( x − y/ 3) . t) = . y) = y2 1 3 + x y + sin( y + x) + sin( x − y/ 3) . t > 0.   . we try to use the boundary value along the t-axis. 0. t) = = = = ( 47) ( 48) ( 49) ( 50) 0. To determine φ and ψ for x < 0. The formula would be  Zx+ct  1 1  g( y) dy x > c t [ f( x + c t) + f( x − c t) ] + 2 c x − ct 2 u( x . 2 2c 0 ( 57) ( 58) But what about φ( x) for x < 0? It turns out that since we only need u( x . x + c t is always positive. 06 x< ∞ c φ( c t) + ψ( − c t) = 0. S emi-infinite string with a fixed end. we need to require the consistency condition f( 0) = g( 0) = 0 and f 00 ( x) = 0. 0) u t ( x . 06 x<∞ g( x) φ 0 ( x) − ψ 0 ( x) = . Remark 4. Initial-boundary value problems.then gives C1 + C2 = 0. Finally u( x . ( 52) ( 53) ( 54) From the first two equations we obtain  g( x) 1 f 0 ( x) + 2 c  g( x) 1 ψ 0 ( x) = f 0 ( x) − 2 c φ 0 ( x) = which gives us φ( x) = 1 1 f( x) + 2c 2 Zx 0 g( y) + C . ( 59) Zx+ct  1 1  g( y) dy 0 6 x < c t [ f( x + c t) − f( c t − x) ] + 2 c ct− x 2 . We consider the case u t t − c2 u x x u( x . 0 6 x < ∞. t > 0 f( x) . x < 0. 0 < x < ∞. 0 6 t < ∞. Obviously to obtain continuous solutions. 0) u( 0. 2. 06 x< ∞ ( 55) . 06 x< ∞ ( 56) ψ( x) = 1 1 f( x) − 2 2c Zx 0 g( y) − C but only for x > 0. t) for x > 0. 4 4 24 8 ( 45) This can be further simplified to u( x . Again we try to fix the two arbitrary functions in the formula ( 51 ) φ( x + c t) + ψ( x − c t) . 3 4 4 ( 46) 2. 1 . Using the initial-boundary values we have φ( x) + ψ( x) = f( x) . g( x) .

0) = f˜ ( x) . 0 6 x < ∞. 0 6 x < ∞. ( § 5. Solution. ( 64) u( x . 0) = g˜ ( x) . 0. − ∞ < x < ∞. we have Z 1 x+2t 1 g( y) dy [ f( x + 2 t) − f( 2 t − x) ] + 4 2t− x 2 Z i 1 x+2t 1h 4 4 = 0 dy ( x + 2 t) − ( 2 t − x) + 2 4 2t− x h  1 = x 4 + 8 x 3 t + 24 x 2 t 2 + 32 x t 3 + 1 6 t 4 2  − x 4 − 8 x 3 t + 24 x 2 t 2 − 32 x t 3 + 1 6 t 4 ) = 8 x 3 t + 32 x t 3 . − ∞ < x < ∞. t > 0 0 6 x < ∞. When x < 2 t. ( 60) ( 61 ) ( 62) ( 63) 0 < x < ∞. 0) u t ( x . ( 74) x − ct for x > 0. − f( − x) x 6 0 − g( − x) x 6 0 ( 66) ( 67) ( 68) ( 69) ( 70) and solve the initial value problem u˜ t t = c 2 u˜ x x . t) = = = = c2 u x x . ( Note that there are several typos in the book) . 0) u t ( x . g˜ ( x) = . 7) Determine the solution of the initial-boundary value problem ut t u( x . g( x) . u˜ t ( x . t > 0. We apply the formula. First in this problem c = 2. Show that one can solve it by extending f . 0. f( x) = x 4 . u˜ ( x . t) = ( 65) Example 6. t) = = = = 4 ux x . When x > 2 t. We extend f and g:   f( x) x> 0 g( x) x> 0 f˜ ( x) = . 1 2. 0 6 x < ∞. x 4. t) = f ( x + c t) + f˜ ( x − c t) + 2 2c From this we clearly have    u( x . t) = g( y) dy [ f( x + 2 t) + f( x − 2 t) ] + 2 4 x− 2t Z i 1 x+2t 1h 4 4 = 0 dy ( x + 2 t) + ( x − 2 t) + 2 4 x− 2t = x 4 + 24 x 2 t 2 + 1 6 t 4 . 0. ( § 5. 0) u( 0. t > 0 ( note that x + c t is always > 0) Zx+ct 1 1 g( y) dy x > c t [ f( x + c t) + f( x − c t) ] + 2 c x − ct 2 . t > 0. t) =   Zx+ct g˜ ( y) dy. Zx+ct 1 1 g( y) dy 0 6 x < c t [ f( x + c t) − f( c t − x) ] + 2 c ct− x 2 ( 75) . 0) u( 0. 0 < x < ∞ . Solution. 1 2. t > 0. t > 0. − ∞ < x < ∞ .Example 5. f( x) . g oddly. ( 71 ) ( 72) ( 73) The d’ Alembert formula gives i 1h ˜ 1 u˜ ( x . 1 0) Consider the initial-boundary value problem ut t u( x . we have Z 1 1 x+2t u( x . g( x) = 0.

Similar to the above case. 0) u t ( x . 0 6 x < ∞ . The problem is u t t − c2 u x x u( x . 1 2. x3. 0. g = x 3 . we obtain φ( x) + ψ( x) = f( x) . Zx+3t g( y) dy x− 3t ( 91 ) . t) = = = = 9 ux x . t > 0 f( x) . φ 0 ( c t) + ψ 0 ( − c t) = 0 1 1 0 f ( − x) − g( − x) 2c 2 x> 0 ψ( x) = 1 1 f( − x) + 2 2c Z− x g( y) + C 0 ( 84) x< 0 ( 85) The constant C 0 is determined by requiring ψ( x) to be continuous. t) = = = = ( 76) ( 77) ( 78) ( 79) 0. 0) u t ( x . 0. therefore C 0 = − C. Using the formula we have when x > 3 t. 0) u x ( 0. g( x) . 0) u x ( 0. ψ( x) = 0 ( 81 ) x> 0 ( 82) 1 1 f( x) − 2 2c Zx 0 ( 83) g( y) − C ψ 0 ( x) = − φ 0 ( − x) for x < 0. 0. 0 < x < ∞. φ 0 ( x) − ψ 0 ( x) = c which gives φ( x) = 1 1 f( x) + 2 2c For ψ( x) with x < 0. we use This leads to ψ 0 ( x) = − Zx g( y) + C .2. 0 6 x < ∞ . t) = . f = 0. Here c = 3. 0 6 t < ∞. ( 86) Zct− x  1 1  g( y) d y + g( y) dy 0 6 x < c t [ f( x + c t) + f( c t − x) ] + 2 2c 0 0 Example 7. t) = φ( x + c t) + ψ( x − c t) Now using the initial value. ( § 5. S emi-infinite string with a free end. 8) Determine the solution of the initial-boundary value problem ut t u( x . u( x . ( 87) ( 88) ( 89) ( 90) 0 < x < ∞. that is the two formulas should yield the same value at x = 0. t) = = = = = 1 1 [ f( x + 3 t) + f( x − 3 t) ] + 2 6 Zx+3t 1 y 3 dy 6 x− 3t i 1 h 4 4 ( x + 3 t) − ( x − 3 t) 24  1  24 x 3 t + 21 6 x t 3 24 x 3 t + 9 x t3 . 2. g( x) . t > 0 06 x<∞ 06 x< ∞ 06 t< ∞ Solution. Putting everything together we have  Zx+ct  1 1  g( y) dy x> ct f( x + c t) + f( x − c t) + [ ] 2 2 c x − ct  Zx + ct  u( x . we first write ( 80) u( x .

0 6 x < ∞ . 0) u t ( x . t) = = = = 0. [ f( x + c t) + f( c t − x) ] + 2c 2 0 0 0 3. t) = . 0) u t ( x . 0) u x ( 0. t > 0 f( x) . ( 93) ( 94) ( 95) ( 96) Remark 8. 0 6 t < ∞. 0) u( 0. t) = [ f( x + 3 t) + f( 3 t − x) ] + 6 2 0 0 # " Z Z3t− x x+3t 1 = y 3 dy + y 3 dy 6 0 0 i 1 h 4 4 = ( x + 3 t) + ( 3 t − x) 24  1  = 2 x 4 + 1 08 x 2 t 2 + 1 62 t 4 24 1 4 9 2 2 27 4 = x + x t + t . g( x) . 0 6 x < ∞ . We obtain ψ( x) = φ( − x) − c Z − x/c 0 q( y) d y − C. ( 1 00) ( 1 01 ) ( 1 02) ( 1 03) ( 1 04) ( 1 05) . t) = = = = 0. g( x) . 0 < x < ∞. Equations with nonhomogeneous boundary conditions. ψ( x) = p − c As a consequence.when x < 3 t. The consistency conditions are p( 0) = f( 0) . # " Z Z3t− x x+3t 1 1 g( y) d y + g( y) dy u( x . 3. and the solution for x < c t is given by  Zx + ct  Zct− x Zt− x/c 1 1 g( y) dy + g( y) dy − c q( y) dy. 0 < x < ∞. 0 6 x < ∞ . Consider u t t − c2 u x x u( x . 0 6 x < ∞ . for x < 0 we obtain  x − φ( − x) . q( t) . p0 ( 0) = g( 0) . Vibration of finite string with fixed ends. 12 2 4 ( 92) 2. 0 6 t < ∞. the formula becomes  Zx+ct  1 1  g( y) d y x> ct [ f( x + c t) + f( x − c t) ] + 2 c x − ct 2 u( x . Zx+ct   1 x 1  g( y) d y + p t − 06 x< ct [ f( x + c t) − f( c t − x) ] + 2 c 2 c ct− x ( 97) ( 98) ( 99) Our last case is u t t − c2 u x x u( x . p( t) . t > 0 f( x) . The approach is similar to that in the homogeneous case. p00 ( 0) = c 2 f 00 ( 0) .

0. ( 1 21 ) As we need u( x . t) : x + c t. Repeating this process. l] while φ over [ 0. 0 6 x < l . 0. t) = φ( x + c t) + ψ( x − c t) and try to exclude arbitrariness using the initial and boundary values. This time. ψ( x) = f( x) − g( y) dy − C . t) = φ( x + 2 t) + ψ( x − 2 t) . 06 t< ∞ 0. 3 l ] . we conclude Z 1 x 1 1 3 φ( x) = y ( 1 − y) dy + C = x 2 − x +C ( 1 22) 4 8 12 1 1 3 ψ( x) = − x 2 + x − C. g = x ( 1 − x) . t) : 0 6 x 6 l . t > 0. ( 1 1 3) What to do for points outside? We need to use the boundary conditions. 0) u t ( x . Now using these two relations again. 2 l] . Using them we obtain ψ( x) = − φ( − x) . In this problem c = 2. g( x) . we obtain ψ over [ − 2 l . Once more we start with the general solution (111) u( x . ∞ ) . ( § 5. t > 0. we finally got ψ defined over ( − ∞ . 0 6 x < l . l ] while φ over [ 0. t) u( 1 . 0) u( 0. ( 1 23) 8 12 Both formulas hold only for 0 6 x 6 1 . 0) u t ( x . u t t − c2 u x x u( x . t) u( l . t) = 0 we obtain using u( 1 . x − c t ∈ [ 0. t) = = = = = 4 ux x . we need values of φ( x) for all x > 0 and ψ( x) for all x < 1 . f = 0. 0. 1 5) Find the solution of the initial-boundary value problem ut t u( x . 0 6 x 6 1. t) for all 0 < x < 1 . t > 0. x ( 1 − x) . It is clear that this is sufficient for determine u( x . l] and that of φ to [ 0. ( 1 1 6) ( 1 1 7) ( 1 1 8) ( 1 1 9) ( 1 20) Solution. 0 6 t < ∞. t) = = = = = ( 1 06) ( 1 07) ( 1 08) ( 1 09) ( 1 1 0) 0. from the initial values we can only obtain Zx Zx 1 1 1 1 φ( x) = f( x) + g( y) dy + C . t) = φ( x + c t) + ψ( x − c t) ( 1 1 5) Example 9. φ( x) = − ψ( 2 l − x) ( 1 1 4) which extends the definition of ψ to [ − l . ( 1 24) ( 1 25) Thus we will use ψ( x) = − φ( − x) and φ( x) = ψ( 2 − x) to determine values of φ and ψ outside 0 6 x 6 1 . 0. u( x . . 0 < x < l. Now using u( 0. t > 0 0 6 x 6 1. 0) u( 0. t) = 0 we obtain φ( c t) + ψ( − c t) = 0 φ( 1 + c t) + ψ( 1 − c t) = 0 ψ( x) = − φ( − x) . First using the initial values. 1 2. 0 < x < 1. t > 0 f( x) . ( 1 1 2) But this only gives us the solution inside { ( x . t > 0. l ] } . t) using for all ( x .A more complicated problem is when we have two boundaries. φ( x) = − ψ( 2 − x) . 2 2c 0 2 2c 0 0 6 x 6 l. Recall that the general solution is u( x .

Using the linearity of the equation. u t ( x . we easily see that w solves w t t − c 2 w x x = h( x . As we can see from the past few lectures. t) . Remark 1 0. x∈ R x ∈ R. t) . u( x . ( 1 34) v( x . x ∈ R. ( 1 26) Next using φ( x) = − ψ( 2 − x) we have φ( x) = and φ( x) = 1 1 2 3 ( 2 − x) − ( 2 − x) + C 8 12 1 6 x 6 2. x∈ R v t ( x . t 0 ) . 1 1 1 1 2 3 2 3 ( 2 − x) + ( 2 − x) + C = ( x − 2) − ( x − 2) + C 12 8 12 8 ( 1 27) 2 6 x 6 3. x ∈ ( x 0 − c ( t 0 − t) . ( 2 + x) + ( 2 + x) − C 8 12 1 1 1 1 3 3 ψ( x) = − ( 2 + x) + ( − x − 2) − C = − ( 2 + x) − ( 2 + x) − C. ( 1 41 ) . t> 0 ( 1 38) ( 1 39) ( 1 40) All we need to do is to solve w. and treat them just as the two coordinate variables for the plane. Nonhomogeneous wave equations. 0) = 0. Nevertheless. x∈ R x ∈ R. we see that φ and ψ are in fact obtained from periodic extension of their values over 0 6 x 6 2 and − 1 6 x 6 1 . 8 12 12 8 ψ( x) = − ( 1 29) ( 1 30) Comparing the values of ψ over − 1 6 x 6 1 and − 3 6 x 6 − 1 . x ∈ R. the closed solution formulas are less and less helpful in understanding the equation/ solution as the domain gets more complicated.Using ψ( x) = − φ( − x) once. 0) = 0. we observe that ψ on − 3 6 x 6 − 1 can be obtained from ψ over − 1 6 x 6 1 by a translation. 0) = g( x) . we can try to simplify the equation a bit using the d’ Alembert formula. In this section we consider the initial value problem u t t − c 2 u x x = h( x . t) : t > 0. t> 0 ( 1 31 ) ( 1 32) ( 1 33) Note that this time we do not have the formula for general solutions at hand. t) = φ( x + c t) + ψ( x − c t) = [ f( x + c t) + f( x − c t) ] + 2 c x − ct 2 We know that v solves v t t − c 2 v x x = 0. 0) = f( x) . w( x . w t ( x . In a few weeks. x ∈ R. x ∈ R. To find out w( x 0 . x 0 + c ( t 0 − t) ) } . ( 1 35) ( 1 36) ( 1 37) Let w = u − v. 0) = f( x) . 4. t > 0 v( x . ( 1 28) Note that so far we have determined ψ on − 1 6 x 6 1 and φ on 0 6 x 6 3. we will study a different approach to these “more complicated” initial-boundary value problems. 0) = g( x) . we can determine ψ on − 3 6 x 6 − 1 : 1 1 2 3 − 2 6 x 6 − 1. we obtain ψ( x) = − 1 3 1 2 x − x −C 12 8 − 1 6 x 6 0. respectively. In the following we will forget the physical meaning that t is time and x space. Let v be defined by the d’ Alembert’ s formula Zx + ct 1 1 g( y) dy. we integrate the equation over the domain of dependence: Ω ≡ { ( x . Carrying on the process. Now using ψ( x) = − φ( − x) again.

We represent Γ 2 by { ( x( t) . We evaluate the integrals on them one by one. w t F dy − G dx ( 1 43) c 2 w x dt + w t dx. t 0 ) . x) dx 0 Z0 G( 1 . Remark 1 2. One way to remember Green’ s formula is the following. t) dx( t) c 2 w x ( x( t) . x) dx + 0 G( 0. x) dx 1 # ( 1 45) F dy − G dx. Then # # ZZ Z1 " Z1 Z1 " Z1 Fx + G y dx dy = Fx dx dy + G y dy dx Ω 0 = Z1 0 = Z1 0 F( 1 . Thus Γ = 0. An equivalent approach is to use Gauss’ theorem instead of Green’ s formula. t) dt + w t ( x( t) .We have ZZ 2  w t t − c w x x dx dt = Ω Now we use Green’ s formula ZZ y. Along it we have dy = 0 and w t = 0. ZZ I Ft + G x dx dt = Fn t + G n x ds Ω ( 1 48) Ω ∂Ω ( 1 49) . t) = 1 2c ZZ h( y . Consider the special case that Ω = { ( x . t) dx dt = − Ω c 2 w x dt + w t dx = 2 c w( x 0 . Ω I Fx + G y dx dy = Ω to obtain ( with t ZZ ∂Ω Remark 1 1 . y) d y − F( 1 . ( 1 44) ∂Ω G. t 0 ) − w( x( 0) . x) dx − " 0Z 1 Z1 G( 0. y) dy + 0 Z0 1 F( 0. t) dt = dt 0 Z t0 d = −c w( x( t) . − c 2 w x F) ZZ I h( x . t) dt dt 0 = − c [ w( x( t 0 ) . y) dy − Z1 G( 1 . t) dx dt = − Ω ( 1 42) h( x . t) } with x( t) + c t = x 0 + c t 0 . 0) ] = − c w( x 0 . t) + w t ( x( t) . y) d y + 0 = I ∂Ω Z1 0 0 F( 0. Then we have dt = − c and Z t0 Z Z t0 w t ( x( t) . Γ 3 along x − c t = x 0 − c t 0 . t) dt + c 2 w x dt + w t dx = Γ2 Z0 t 0 Z0 t 0 = c 2 w x ( x( t) . t) ( − c) dt 0 0   Z t0 dx( t) − c w x ( x( t) . y) : 0 < x . ( 1 46) Γ 3 is similar to Γ 2 . The boundary ∂Ω can be consists of three parts: Γ 1 along the x-axis. s) dy ds. t 0 ) ( 1 47) ∂Ω which gives the formula w( x . t) dx dt. R • Γ 1 . Putting the three parts together we obtain ZZ I h( x . 1 • • dx ( t) Γ 2 . Γ 2 along x + c t = x 0 + c t 0 . y < 1 } .

( 1 54) ( 1 55) Note. √ therefore we finally have ( 1 50) c2 ( 1 51 ) ( 1 52) ( 1 53) Ω The general formula for non-homogeneous problem is then Zx+ct ZZ 1 1 1 g( y) dy + u( x . 7. Please take a few minutes to compare ( 5. t) dx dt. which means 1+ dt 1 =±√ . y ∈ ( x − c ( t − s) . ( 1 60) . 1 2. we have along them. 0) = 0. 0) = x . = 1 nx √ As a consequence. t) = { ( y . n x are the t-component and x-component of the outer normal n. 2 6 c Substituting back into the equation. 0) = sin x . t) = x + c t. t) 1 c 1 = x + sin x sin c t + x t 2 + t 3 . Taking F = w t and G = − c 2 w x . Example 1 3. 7. ( § 5. s) : s > 0. 1 1 ) in the book and our formula above. 2 b) ) Solve u t t − c 2 u x x = x + c t. we see that we have found the correct answer. t) 0 = Zt 0 ( 1 56) ( 1 57) x − c( t− s) 2 x c ( t − s) + 2 c 2 s ( t − s) ds 2 = 2 c x t 2 − x c t 2 + c 2 t 3 − c2 t 3 3 1 2 3 2 = cxt + c t . Here f( x) = x. 3 ( 1 58) Thus the solution is Zx + ct ZZ 1 1 1 u( x . t) where Ω( x . Solution. u t ( x . u t ( x . 1 2. We evaluate Zx+ct sin y dy = − [ cos( x + c t) − cos( x − c t) ] = 2 sin x sin c t. 2 e) ) Solve u t t − c2 u x x = x e t . 0) = sin x.where s is the arc length variable along the boundary. Along the two sides we have   c   ±√ nt 1 + c2  . s) dy ds 2c 2 c x − ct 2 Ω ( x . h( x . 1 1 ) is not really useful as the authors forgot to replace h by h ∗ . x − ct and # ZZ Zt " Zx + c( t− s) y + c s dy ds = y + c s dy ds Ω ( x . s) d y ds [ f( x + c t) + f( x − c t) ] + 2 2c 2 c x − ct Ω ( x . u( x . t 0 ) = h( x . ( 1 59) Example 1 4. The solution formula in the book ( 5. and n t . t) = [ f( x + c t) + f( x − c t) ] + h( y . t) = g( y) d y + h( y . u( x . x + c ( t − s) ) } . g( x) = sin x. ( § 5. ds 1 + c2 dx c =− √ ds 1 + c2 c dw 1 wt ∓ √ wx = 2 2 ds 1+c 1+c ZZ 2 c u( x 0 . we have ZZ I  w t t − c 2 w x x dx dt = w t n t − c 2 w x n x ds Ω ∂Ω The boundary ∂Ω consists of three parts.

t) y y = u r r 2 + u r − 3 u r . We have f( x) = sin x. r ( 1 73) r > 0. y . z . 0) = f( r) u t ( r. ( 1 64) ( 1 65) ( 1 66) u t t − c2 ( u x x + u y y + u z z ) = 0 u( x . t) = sin x cos c t + x e t − t − 1 . h( x . One can also consider wave equations in higher dimensions. = 0 where the latter integral is evaluated using integration by parts: Zt Zt Zt   e s ds = t e t − e t − 1 . t) Ω ( x . y . y . where all functions only depends on the radius r = x2 + y2 + z2 . y . t) z z = u r r 2 + u r − 3 u r . For example. 0) = g( x . z) u t ( x . p we will deal with a special case in 3D. Spherical wave equations. Nevertheless. Calculate ZZ ZZ h( y . t > 0 ( 1 74) r> 0 r> 0 ( 1 75) ( 1 76) . z . y) u t ( x . ( 1 63) 5. 0) = f( x .Solution. t) x x = ( u x ) x = ( u r r x ) x = u r = ur r 2 + ur − 3 ur . Using chain rule we obtain  x x2 1 x2 u( r . ( 1 70) r x r r r y2 1 y2 u( r . y . y) . g( x) = 0. t) = x e t . 0) = f( x . 0) = g( x . r r r Using the fact that x 2 + y 2 + z 2 = r 2 we obtain ux x + u y y + uz z = ur r + The equations then become u t t − c2   2 ur = 0 r u( r. z) . y. t) # Z " Z x + c( t− s) t = 0 = Zt Z0 t y e s d y ds x − c( t− s) i 1h 2 2 ( x + c ( t − s) ) − ( x − c ( t − s) ) e s ds 2 2 x c ( t − s) e s ds  Zt  Zt s s = 2xc t e ds − s e ds 0 0   = 2 x c t et − 1 − 2 x c t et + 2 x c et − 1  = 2 x c et − t − 1 . in 2D we have u t t − c2 ( u x x + u y y ) = 0 u( x . s) dy ds = y e s d y ds Ω ( x . ( 1 71 ) r r r 2 2 1 z z ( 1 72) u( r . 0) = g( r) ur r + 2 ur . First we need to re-write the equations so that only t and r appear. s e s ds = s de s = s e s t0 − 0 ( 1 61 ) ( 1 62) 0 0 Putting everything together we obtain the solution  u( x . ( 1 67) ( 1 68) ( 1 69) in 3D we have Solution formulas are also available but their derivation is beyond the scope of our course here.

( 1 81 )  1 1  G( ρ) dρ 0 6 r 6 c t [ F( r + c t) − F( c t − r) ] + 2 2 c ct− r Recalling U = r u. t) = 0 for all t > 0. t) = Zr+ct .This equation can be explicitly solved through the following trick: Let Then we have ( 1 77) U( r . then U( 0. Ut t − c 2 Ur r = 0 U( r . 0) = G( r) ≡ r g( r) r > 0. t) = Zr −r +c tc t  1 1  ρ g( ρ) dρ 0 6 r 6 c t [ ( r + c t) f( r + c t) − ( c t − r) f( c t − r) ] + 2r 2 r c ct− r ( 1 82) . 0) = F( r) ≡ r f( r) Ut ( r . t) . we obtain  Zr+ct  1 1 ρ g( ρ) dρ r > c t  2 r [ ( r + c t) f( r + c t) + ( r − c t) f( r − c t) ] + 2 r c u( r . t > 0 r> 0 r> 0 ( 1 78) ( 1 79) ( 1 80) If we assume u to be bounded. Thus the equation for U can be solved using the formula we have discussed:  Zr+ct  1 1  G( ρ) dρ r > c t [ F( r + c t) + F( r − c t) ] + 2 2 c r − ct U( r . t) ≡ r u( r .